Mapping the research landscape of PET/CT in lymphoma: insights from a bibliometric analysis - Zhang, Die; Peng, Jianding; Zhu, Yingjie; Gong, Qiang; Wang, Qing; Xiang, Chaodong; Du, Hanjian; Hu, Xiaofei (Frontiers in Oncology, 2025)
ObjectiveThis study provides a comprehensive bibliometric analysis of research trends in Positron Emission Tomography/Computed Tomography (PET/CT) applications for lymphoma, aiming to identify key contributors, emerging topics, and collaboration patterns within the field.MethodsData from the Web of Science Core Collection (2004–2024) were analyzed. Original articles and reviews in English on PET/CT in lymphoma staging, response assessment, or prognosis were included, while case reports, meeting abstracts, and editorials were excluded. Using CiteSpace, VOSviewer, and Bibliometrix R, we evaluated country/institutional contributions, co-citation networks, keyword trends, and employed linear regression for trend forecasting.ResultsA total of 2,962 papers related to PET/CT and lymphoma were published during the study period. The annual publication volume increased significantly, peaking in 2021 with 281 papers, followed by a decline to 260 in 2023, potentially linked to COVID-19-related research disruptions. The United States and China led in publication volume, contributing over 40% of global publications. Leading institutions included UNICANCER and Assistance Publique Hôpitaux de Paris. Influential authors such as Sally F. Barrington and Michel Meignan were identified. The European Journal of Nuclear Medicine and Molecular Imaging and the Journal of Nuclear Medicine were the top journals in this field. Key research themes included staging, response assessment, prognosis, and the role of PET/CT in personalized treatment approaches.ConclusionThis bibliometric analysis highlights the significant growth and evolving trends in PET/CT research for lymphoma. The findings underscore the critical role of PET/CT in advancing precision medicine, informing future research directions, and optimizing clinical practices in lymphoma management.